Investigation of Major Diseases and Pests of Coconut and Areca Palm in Wenchang City (Global Journal of Science Frontier Research, 2022)
A systematic investigation was carried out on the diseases and insect pests of coconut and areca palm in Wenchang City of Hain Province from 2019 to 2022. Stem bleeding disease, coconut blackheaded caterpillar (CBC), coconut leaf beetle (CLB), and red palm weevil were found to be the main threats to coconut trees; yellow leaf disease (YLD), leaf yellowing virus disease (LYVD), bacterial leaf spot disease, CLB, and Tirathabarufivena (Walker) were observed to be key restricting factors for the areca palm trees. During this survey, 17 species of plants were found as hosts of CBC; YLD and LYVD were observed in five towns including Wencheng and Chongxing; necrotic ringspot virus disease was discovered for the first time in Wencheng and Huiwen. Currently, As the major diseases and insect pests of coconut and areca palm presents a tendency of increasingly serious trend of in Wenchang City, it is recommended that the agriculture and forestry departments to carry out integrated measures, including regular monitoring, forecasting, and timely prevention and control once an outbreak trend is observed, so as to ensure the sustainable and healthy development of the industries.
Keywords: coconut palm; areca palm; coconut leaf beetle; coconut black-headed caterpillar